Normothermic regional perfusion and US legal standards for determining death are not aligned. Issue 5 (26th February 2022) - Glazier, Alexandra K.; Capron, Alexander M.
Abstract : The claim that Normothermic Regional Perfusion is compatible with circulatory determination of death because physicians do not intend to resuscitate the donor ignores the fact that laws on determining death in all states define a condition and do not include the element of physician or patient intent. See Parent et all (Page 1307 ) and Wall et al. (page 1311 )